Transformasi MIM Bolon menjadi MIM Digdaya Bolon: Langkah Strategis dalam Meningkatkan Kualitas Pendidikan - Khoir, Mulyanto Abdullah; Dewi, Rachma Rusdiana; Sayidah, Aminatus (TSAQOFAH, 2025)
The transformation of MIM Bolon into MIM Digdaya Bolon is a strategic step to improve the quality of education at the basic level through comprehensive changes, not only in the name aspect, but also the curriculum, management and teaching methods. This article examines this transformation process using a qualitative approach and case studies to analyze the steps taken and their impact on the quality of education. This research found that the name change to "Digdaya", which means strength to rise, serves as a symbol of the institution's efforts to improve the quality of education, introduce technology, and increase teacher competency. Apart from that, this transformation also involves developing relevant curricula, better educational facilities, and increasing collaboration with parents and the community. Even though it is faced with challenges such as limited human resources and facilities, MIM Digdaya Bolon has succeeded in creating a learning environment that is innovative and relevant to current developments. The positive impact of this transformation is reflected in the increasing number of students, learning motivation, academic achievement, as well as a more active role of parents in supporting children's education. In this way, MIM Digdaya Bolon has succeeded in improving the quality of education provided for future generations.